Analysis of asthenic phenomens in patients with type 2nd diabetes mellitus in the clinical and psychological aspect - Tkachenko, O. V. (Journal of Education, Health and Sport, 2017)
Aim – to analyze the peculiarities of asthenic manifestations in patients with type 2nd diabetes mellitus (DM) in clinical and psychological perspective. Materials and methods. We examined in 543 patients with type 2nd DM. The first clinical group (CG-1) was 57 patients with type 2nd DM of mild severity; the average age in the group was (51,80±1,28) years. The second clinical group (CG-2) made up of 312 patients with type 2nd DM, moderate severity; mean age in the group was (55,10±1,12) years. The third clinical group (CG-3) included 174 patients with type 2nd DM, severe degree of severity; the average age in the group was (61.80±0,85) years. Research methods: clinical-anamnestic, clinical-psychopathological, statistical. Results. The marked prevalence of asthenic syndrome in patients wath type 2nd DM 52,30%, which is almost half among all surveyed type 2nd DM. Discovered the direct correlation of asthenic symptoms with the severity of the type 2nd DM (rs = 0.4033, p<0.01). The factors in the risk of asthenic syndrome in patients with type 2nd DM was installed, among them is dominated by a moderate and severe degree of type 2nd DM, combined with obesity 2 degrees, DEP II degree, ischemic heart disease, heart failure, degenerative dystrophic lesions of the spine. Established that there is a direct correlation asthenic syndrome to the severity of type 2nd DM, as well as the accompanying somatic pathology. Established dominance in CG-1 and CG-2 component fatigue "mental fatigue" and CG-3 component "physical fatigue". Conclusions. Features of asthenic manifestations in patients with type 2nd DM in clinical and psychological perspective were investigated. The detection rate of asthenic manifestations among patients with type 2nd DM and the factors for their amplification were established. The organic etiology of asthenic manifestations have been proven; presentation about the stages of development of asthenic symptoms in patients with type 2nd DM were improved.